Students' Perception of the Virtual Rock Microscope in the General Geology Course - Jernih Karniat Sari Zai; Susetyo , Bigharta Bekti (Global Action and Education for Society, 2025)
This research aims to determine the perceptions of 2024 geography education students regarding the use of virtual rock microscope learning media in the general geology course based on 6 indicators of student perceptions towards the use of virtual rock microscope. This research is a descriptive quantitative study conducted in the city of Padang with a research sample consisting of 2 classes from the 2024 batch of the Geography Education Study Program, totaling 41 students. The sampling technique in this study used the purposive sampling method. The research results show that 1) the use of a virtual rock microscope in general geology learning meets the good criteria at 86%, 2) the media used clarifies students' understanding of the material presented at 84% good criteria, 3) it provides feedback that is meaningful for students and lecturers during the learning process through the virtual rock microscope at 85% good criteria, 4) it identifies the effectiveness of access and the use of features available in the virtual rock microscope at 85% good criteria, 5) difficulties when using the virtual rock microscope meet the good/no difficulty criteria at 81%, 6) obstacles when using the virtual rock microscope meet the good/no obstacles criteria at 81%. The conclusion of students' perceptions regarding the use of virtual rock microscopes as a learning medium for rock material in the general geology course overall falls into the good or positive category.